2019
DOI: 10.1177/2333794x19876809
|View full text |Cite
|
Sign up to set email alerts
|

How Prepared Are Pediatric Residents for Pediatric Emergencies: Is Pediatric Advanced Life Support Certification Every 2 Years Adequate?

Abstract: Objectives. We assessed pediatric residents’ retention of knowledge and clinical skills according to the time since their last American Heart Association Pediatric Advanced Life Support (AHA PALS) certification. Methods. Sixty-four pediatric residents were recruited and divided into 3 groups based on the time since their last PALS certification, as follows: group 1, 0 to 8 months; group 2, 9 to 16 months, and group 3, 17 to 24 months. Residents’ knowledge was tested using 10 multiple-choice AHA PALS pretest qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In our previous study, we found pediatric residents' code team leadership skills markedly declined within 8 months of their last PALS certification. 20 Our results showed that increasing the frequency of mock codes during pediatric residency training from monthly to weekly, improved pediatric senior residents' team leader performance scores. Residents performed more effectively as code team leaders and the improvement was significant both for the leadership and for their overall performance scores during the mock code.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In our previous study, we found pediatric residents' code team leadership skills markedly declined within 8 months of their last PALS certification. 20 Our results showed that increasing the frequency of mock codes during pediatric residency training from monthly to weekly, improved pediatric senior residents' team leader performance scores. Residents performed more effectively as code team leaders and the improvement was significant both for the leadership and for their overall performance scores during the mock code.…”
Section: Discussionmentioning
confidence: 61%
“…In our previous study, we found pediatric residents’ code team leadership skills markedly declined within 8 months of their last PALS certification. 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown poor retention of knowledge and skills with the current resuscitation training approaches [ 21–24 ]. Declines in knowledge and technical skills have been shown to occur within months of PALS training [ 24 , 25 ]. Our results are therefore unsurprising, and the deviations from established resuscitation guidelines may reflect a systemic issue with regard to our current approaches to resuscitation training.…”
Section: Discussionmentioning
confidence: 99%
“…critical appraisal of the body of literature that compared the effect of training frequency on CPR skill performance, authors concluded, "there is insufficient evidence to confirm an optimal training frequency… [however], annual resuscitation training is insufficient to maintain effective CPR skill performance" [6] (p.823). Similarly, Doymaz, et al [8] assessed pediatric residents' retention of knowledge and clinical skills over time following AHA PALS [5] certification. Authors discovered that participants' clinical skills performance declined within the and Illinois Emergency Medical Services for Children [12]), including fully developed scenarios, extremely valuable.…”
Section: Check For Updatesmentioning
confidence: 99%